Edukasi Pemberdayaan Literasi Kritis Berbasis Cerita Rakyat Digital Pada Siswa Kelas Tinggi - Dhia Asy Syafa; Nur Habibah; Widyaratnasari (Jurnal Berbasis Sosial, 2026)
: The low application of critical literacy in learning in elementary schools is one of the challenges faced by teachers, especially in utilizing digital media that still accommodates local cultural values. This community service activity aims to improve teachers' competence in applying critical literacy through the use of digital folklore in elementary school high school students. The activity was carried out by involving 12 high-class teachers using the Participatory Action Learning (PAL) approach which included needs analysis, education, workshops on the preparation of learning tools, implementation assistance, as well as monitoring and evaluation. Data was collected through observation, questionnaires, tests, and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results of the activity showed an increase in teacher competence, which was shown by the increase in the average score from 61.4 in the pretest to 86.8 in the posttest. All participants were also able to develop learning tools based on digital folklore and implement them in critical literacy learning in the classroom. In addition to improving teachers' ability to utilize digital media, this activity also encourages the integration of local cultural values into the learning process. Thus, critical literacy empowerment education based on digital folklore is one of the effective alternatives to strengthen literacy culture while improving the quality of learning in elementary schools.